Glacial heterogeneity in Southern Ocean carbon storage abated by fast South Indian deglacial carbon release - Julia Gottschalk (Nature Portfolio, 2020)
A Southern Ocean influences on the carbon cycle is considered a key component of deglacial changes. Here, the authors show spatial differences in glacial Southern Ocean carbon storage that dissipated rapidly 14.6 kyr ago, revealing a South Indian Ocean contribution to rapid deglacial atmospheric CO2 increases.